PERAN LAYANAN BIMBINGAN DAN KONSELING KELOMPOK DENGAN TEKNIK ROLE PLAYING DALAM MENINGKATKAN KECERDASAN EMOSIONAL: LITERATURE REVIEW - Wahidatun Nisa; Abdul Muhid (STKIP PGRI SUMENEP, 2022)
Many people believe that a person's life success is determined by intelligence. Actually, the success of a person's life is influenced by one of the factors, namely emotional intelligence. The role of group counseling services is a good help by giving students awareness about a variety of good or healthy behaviors and bad or problematic behaviors. In this review literature study, the researcher chooses the role of group guidance and counseling services using role-playing techniques in enhancing emotional intelligence. From playing the role of students able to recognize their emotions, process their emotions, and be able to establish good relationships with others with the help of counseling teachers in the school in helping the counseling process. Therefore, this literature study research aims to review the role of group counseling services using role-playing techniques in enhancing emotional intelligence. The literature study results showed that the role of group guidance and counseling services using this role-playing technique greatly affects the improvement of emotional intelligence.